Representation of Indonesian Women Beauty in Citra Handbody Lotion TV Ads "Dari Citra Untuk Perempuan Indonesia" - Febri Dwi Ratna Sari (Jurnal Sosioteknologi, 2016)
Beautiful generally can be interpreted as something that is pretty, good, and fascinating. Beautiful itself is a representation that deliberately created by the media  so that the public would  believe what pretty is. One of media that is used for spreading it was advertising. In advertising there are meanings and myths used to create beliefs regarding about  advertising's  messages to society. The purpose of this study to determine the meaning of denotation, connotation and myth which contained in Handbody Citra Lotion's television advertision. This study uses qualitative, semiotic analysis of Roland Barthes. Based  on the research results, the conclusions drawn in the denotative meaning of Citra product  from Citra Handbody lotion's advertising that Citra  products uphold the culture and the cultural heritage of Indonesia, especially the beauty of women in Indonesia. There is also connotation meaning about beauty of Indonesian women from different regions based on their culture. For the myth's meaning is the myth about beauty of Indonesian women are besed on their customs and culture.